"Fortress Europe is an insult to the values of the EU": The legitimation of migrant acceptance in the human security speech acts of Members of the European Parliament. Issue 1 (3rd November 2022) - Krotký, Jan
Abstract: Scholars agree that securitized discourses mainly drive migration policy. However, to fully understand the migration discourse, it is necessary to look also at the discourse legitimating the acceptance of migrants, refugees, and asylum seekers. Namely, how Members of the European Parliament (MEPs) legitimate the potential acceptance of migrants in EU plenary debates within the human security speech acts that prevail in the European Parliament plenary debates. By exploring legitimation categories, I show that human security discourse might remain part of the exclusion process, similarly to other security concepts and discursive strategies. In other words, the results show that in human security speech acts, MEPs evoke the "language of exclusion practices" containing the victimhood trope and building the "hierarchy of vulnerability." Moreover, MEPs' efforts to legitimize immigration in this way might be counterproductive. In particular, the article discusses whether attempts to elicit grand emotions such as pity or shame helps to attract the audience. 摘要: 学者一致认为，关于安全化的话语主要能推动移民政策。不过，为了充分理解移民话语，也有必要分析对"接受移民、难民和寻求庇护者一事"加以合法化的话语。具体而言，欧洲议会成员（MEP）如何通过欧洲议会全体辩论中普遍存在的人类安全演讲，对移民的潜在接受度进行合法化。通过探究合法化类别，我论证认为，人类安全话语可能仍然是排除过程的一部分，类似于其他安全概念和话语策略。换句话说，结果表明，欧洲议会成员在人类安全演讲中唤起了一种"排斥实践语言"，后者包含受害者比喻并建立了"脆弱性等级"。此外，欧洲议会成员在"以这种方式使移民合法化"上所作的努力可能会适得其反。特别地，文章探讨了那些试图引起怜悯或羞耻等情绪的尝试是否有助于吸引受众。 Resumen: Los académicos están de acuerdo en que los discursos securitizados impulsan principalmente la política migratoria. Sin embargo, para comprender completamente el discurso migratorio, es necesario observar también el discurso que legitima la aceptación de migrantes, refugiados y solicitantes de asilo. A saber, cómo los miembros del Parlamento Europeo (MEP) legitiman la posible aceptación de inmigrantes en los debates plenarios de la UE dentro de los discursos sobre seguridad humana que prevalecen en los debates plenarios del PE. Al explorar las categorías de legitimación, muestro que el discurso de la seguridad humana puede seguir siendo parte del proceso de exclusión, de manera similar a otros conceptos de seguridad y estrategias discursivas. En otras palabras, los resultados muestran que, en los actos de discurso de seguridad humana, los eurodiputados evocan el "lenguaje de las prácticas de exclusión" que contiene el tropo de victimización y construye la "jerarquía de la vulnerabilidad." Además, los esfuerzos de los eurodiputados por legitimar la inmigración de esta manera podrían ser contraproducentes. En particular, el artículo analiza si los intentos de provocar grandes emociones como la lástima o la vergüenza ayudan a atraer a la audiencia.